Left ventricular mass index and sports: the influence of different sports activities and arterial blood pressure - Iglesias Cubero, G.; Batalla, A.; Rodriguez Reguero, J. J.; Barriales, R.; Gonzalez, V.; de la Iglesia, J. L.; Terrados, N. (International Journal of Cardiology, 2000)
Background: The mechanisms by which endurance training produces physiological hypertrophy have been thoroughly investigated but not with young athletes. The aim of our study was to investigate arterial blood pressure exercise responses in young athletes who started heavy training by the age of 11, participating in metabolically different sports (cycling, kayaking, and soccer) and to analyse the influence that arterial blood pressure at maximum exercise and VO(2) max could have on the development of cardiac mass in these subjects. Subjects and methods: We studied a group of well trained normotensive male subjects, comprising 37 cyclists, 15 soccer players and 12 canoeists (mean age, 16+/-1 years). Evaluation included a clinical history and physical examination, M-mode and two-dimensional echocardiography, 12-lead resting electrocardiogram and a graded exercise test with direct determination of VO(2) max. Systolic and diastolic blood pressure were measured at rest and maximum exercise. Determination of the left ventricular mass index (LVMI) was performed using Devereux's formula with correction for the body surface area. Results: Cyclists showed values of LVMI in g m(-2) significantly higher than those of other subjects (123 vs. 92 and 113). Canoeists showed the maximal arterial blood pressure at maximum exercise in mmHg (190 vs. 172 and 170) and cyclists showed the maximal VO(2) ml kg(-1) min(-1) uptake (57.6 vs. 48.5 and 53.3). A linear correlation was found between LVMI and VO(2) max (r=0.4727, P<0.001) and this correlation was also significant with systolic blood pressure at maximum exercise (r=0.2909, P<0.01). No differences in LVMI were found when comparing those subjects who presented systolic blood pressure at maximum exercise equal or greater than 195 mmHg with those who presented less than this value. Conclusions: It can be concluded that VO(2) max is the variable that better correlates with the LVMI. Athletes who reach greater systolic blood pressures at peak exercise have a tendency to develop greater LVMI. In comparison with soccer players and canoeists, cyclists are the sportsmen who develop a greater LVMI and VO(2) max.